The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0100-204x2015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for drought-tolerance in cassava

Abstract: -The objective of this work was to evaluate the effect of drought on genetic parameters and breeding values of cassava. The experiments were carried out in a completely randomized block design with three replicates, under field conditions with (WD) or without (FI) water deficit. Yield of storage roots (RoY), shoot (ShY), and starch (StY), as well as the number of roots (NR), and root dry matter content (DMC) were evaluated in 47 cassava accessions. Significant differences were observed among accessions; accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
3
27
0
6
Order By: Relevance
“…However, there was no significant difference for NRRP and FRY. Genetic variation for cassava root traits, including root yield, has been commonly identified in different studies in Brazil (Barreto & Resende, 2010;Oliveira et al, 2014Oliveira et al, , 2015 and in Africa (Aina et al, 2007;Ojulong et al, 2008;Tumuhimbise et al, 2015). Possibly, in the present study, the augmented blocks design was not suitable to detect differences for root yield.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…However, there was no significant difference for NRRP and FRY. Genetic variation for cassava root traits, including root yield, has been commonly identified in different studies in Brazil (Barreto & Resende, 2010;Oliveira et al, 2014Oliveira et al, , 2015 and in Africa (Aina et al, 2007;Ojulong et al, 2008;Tumuhimbise et al, 2015). Possibly, in the present study, the augmented blocks design was not suitable to detect differences for root yield.…”
Section: Resultsmentioning
confidence: 67%
“…This indicated that SCR had low environmental effect on local conditions, and evaluations of SCR in a higher number of divergent cassava genotypes may guarantee better results of genetic selection for this trait. Higher values of CVe for starch yield were detected by Oliveira et al (2014Oliveira et al ( , 2015. However, estimates of CVg for starch yield were low for a sample of 250 cassava genotypes assessed in the state of Amazonas, Brazil (Barreto & Resende, 2010).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations